Effect of crocin on PKHD1 and KLLN genes expression in kidney tissue of female rats treated with cadmium (International Journal of Medical and Surgical Sciences, 2020)
According to data from studies, antioxidant herbal compounds are, likely to have a useful role in reducing the harmful effects of environmental pollutants and toxic chemicals that most people are exposed to. Cadmium is one of the toxic elements that accumulate in many organs, especially in kidneys. The aim of this study was to investigate the effect of crocin on the expression of PKHD1 and KLLN genes in cadmium-treated rats.In this experimental study, 40 adults male Wistar rats (200-250 g) were randomly divided into the following groups: control group received normal saline, cadmium group (15mg/kg), crocin group (20mg/kg) and cadmium group daily fed with crocin at a dose of 20 mg/kg.After eight weeks of treatment, rats were dissected, and kidney tissues were removed for evaluation of PKHD1 and KLLN gene expression by real time method. The data were analyzed using oneway ANOVA and significant difference between groups was P